Indomie Product Marketing Strategy in Entering International Marketing: Indomie Product Marketing Strategy In Entering International Marketing - Wildan Izzaty; Nuri Aslami (International Journal Labs, 2021)
The company needs to prepare a strategy to market its products in order to penetrate the international market. Market competition is so much a challenge for entrepreneurs. In this case, one of the companies that is able to survive with intense competition and successfully penetrate the international market is PT. Indofood Makmur is a company engaged in food and beverage processing. The brand name used by PT Indofood CBP Sukses Makmur Tbk, is Indomie. first time comes with Chicken Broth Flavor only. In Indonesia, the term